شیكردنهوەی شوێنی بۆ گهشهی دانیشتوانی قهزای دەربهندیخان له ماوەی نێوان سانی (١٩٧٧-٢٠٢٠ (دا - تالیب, جهزا تۆفیق; حمه, سروە جلال; احمد, شۆخان محمد (Sulaimani Journal for Humanities, 2021)
Conducting research on population growth is deemed as one of the demographic phenomena that are taken into the account of the planners as a response to the ever-increasing needs associated with the population increase, so that we can make the due palnning process through this.Based on that, we have chosen the district of Darbandeexan to look for the spatial analysis between the years (1977-۲۰۲۰), being compared and contrasted to the population growth of Sulaimany Governorate with the purpose of showing the difference of population growth during different periods. The current study deals with the numerical, relative and environmental distribution of population according to administrative units, in addition to the population density having been delineated. Looking for the population growth between (1977-1987) shows that the annual growth ratio for the district had amounted to (9.8%), while that of the Governaorate had reached to (3.3%). Afterward, and within the years (1987-2002) it had decreased on the lelvel of the district amounting to (-4.54%), keeping in mind the fact that Darbandeexan district was not following Sulaiamny Governorate administratively in (2002). But between (2002-۲۰۲۰) the annual growth ratio for the district had raised to (۳٫٦۷%). The annual growth ratio for both the district and the governorate had , as well, gone up reaching to (۲٫۱%) and (۲٫٦%) for both of them respectively between (1977-۲۰۲۰).The reason for that fluctuation of ratios during the research period belongs to the administrative and political factors that impinged the population of the district and governorate, in addition to moving of people from rural areas to the cities. The study has come to conclusion that the ratio of rural population had increased and reached to (39.7%) in (1977) enumeration ,then ever increased to (91.8%) in(2009)census.While the ratios of rural population decreased to (60.3%) at (1977) and to (۸.2%) at (۲۰۲۰).This can be accounted for by the job opportuinties in cities which lead to the flowing of rural people to the cities .Moreover, the study concludes that the general density of the district population at (1977) amounted to (43 person/ km2 ), and later on at (۲۰۲۰) this density had amounted to(۱۰۳ person/ km2 ). In respect to the rural density in the study region , it reached to (79.5 person/ km2 ) at (1977) and later on,in (2009) the rural population density had increased to (57 person/km2 ).